Exploring Chiropractic Services in the Canadian Forces Health Services – Perceptions of Facilitators and Barriers Among Key Informants. Issue 5 (21st November 2018) - Mior, Silvano A; Vogel, Ellen; Sutton, Deborah; French, Simon; Côté, Pierre; Nordin, Margareta; Loisel, Patrick; Laporte, Audrey
Abstract: Introduction: Musculoskeletal (MSK) conditions have a significant impact on the health and operational readiness of military members. The Canadian Forces Health Services (CFHS) provides a spectrum of health services in managing Canadian Armed Forces (CAF) personnel health care needs with on-base and off-base services provided by civilian and uniformed health care professionals, including chiropractors. Although chiropractic services are available in US DoD and VA systems, little is known about the facilitators and barriers to integrating on-base chiropractic services within the CFHS. This study explored key informants' perceptions of facilitators and barriers to the integration of on-base chiropractic services within the CFHS. Methods: We conducted a qualitative study to describe and understand how an integrated chiropractic service could be designed, implemented, and evaluated within the current interdisciplinary CFHS. Telephone interviews were conducted, using a semi-structured interview guide, to explore key informants' perceptions and experiences of chiropractic care within the CFHS. In total, we invited 27 individuals across Canada to participate; 15 were identified through purposeful sampling, 12 through a snowball sampling technique, and 2 declined. The 25 participants included military personnel (52%), public servants and contractors employed by the Department of Defense (24%), as well as civilian health care providers (24%). All participants were health care providers [physicians (MD) (7), physiotherapists (PT) (13), chiropractors (DC) (5)]. Interviews were audio-recorded and transcribed verbatim. Transcripts were prepared and analyzed using an interpretivist approach that explored key informants' perceptions and experiences. Results: Qualitative analysis revealed numerous facilitators and barriers to chiropractic services in the CFHS. These were categorized under three broad themes: base-to-base variations, variable gatekeeper roles, and referral processes. Barriers to integrating chiropractic services included: lack of clarity about a chiropractor's clinical knowledge and skills; CFHS team members' negative prior experiences with chiropractors (e.g., inappropriate patient-focused communication, clinical management that was not evidence-based, ignorance of military culture); suboptimal bi-directional communication between CAF personnel and DCs across bases; and wide-ranging perspectives pertaining to duplication of services offered by PTs and DCs in managing MSK conditions. Facilitators associated with the integration of chiropractic services within a collaborative and interdisciplinary CAF environment included: patient benefits associated with multiple approaches utilized by different providers; adoption of up-to-date, high-quality evidence and guidelines to standardize care and curtail "dependency" between patient and providers; and co-location of providers to strengthen existing interprofessional communication and relationships. Key informants called for patient care that is collaborative, integrated and patient-centered, rather than "patient-driven" care; civilian providers understanding and respecting military culture rather than assuming transferability of patient management processes from the public civilian sector; standardization of communication protocols and measures to evaluate outcomes of care; and the need to move slowly and respectfully within the current CAF health care system if planning the on-base implementation of chiropractic services. Conclusion: This study illuminated many opportunities and barriers, in complex and diverse domains, related to introducing collaborative chiropractic services in the CFHS. The findings are relevant to increasing understanding and strengthening interprofessional collaborative care within the unique CAF health care delivery system.